Cochrane Database of Systematic Reviews 2008
DOI: 10.1002/14651858.cd004083.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Peribulbar versus retrobulbar anaesthesia for cataract surgery

Abstract: There is little to choose between peribulbar and retrobulbar block in terms of anaesthesia and akinesia during surgery in terms of acceptability to patients, need for additional injections and development of severe complications. Severe local or systemic complications were rare in PB and RB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 22 publications
1
26
0
1
Order By: Relevance
“…The applicability of metaanalysis for the study undertaken by Alhassan et al 108 is probably justified as the number of patients in their study was large (N Z 221) compared with the number in the study by Friedman et al 27 (N Z 40). Also, the statistical power of the study by Alhassan et al exceeds that of the study by Friedman et al However, as the available data for the comparative study of the patient-perceived pain for most of the local anesthetic modalities are limited, it is prudent to be guided by the methodology adopted by Friedman et al 27 There is, however, a trend to use random-effect modeling to accommodate the significant heterogeneity assumption and thereby justify the use of metaanalysis, but the inherent weakness of this method is that the sources of bias are not controlled by the method.…”
Section: Comparative Evaluation Of Local Anesthesia Techniques Patienmentioning
confidence: 95%
See 3 more Smart Citations
“…The applicability of metaanalysis for the study undertaken by Alhassan et al 108 is probably justified as the number of patients in their study was large (N Z 221) compared with the number in the study by Friedman et al 27 (N Z 40). Also, the statistical power of the study by Alhassan et al exceeds that of the study by Friedman et al However, as the available data for the comparative study of the patient-perceived pain for most of the local anesthetic modalities are limited, it is prudent to be guided by the methodology adopted by Friedman et al 27 There is, however, a trend to use random-effect modeling to accommodate the significant heterogeneity assumption and thereby justify the use of metaanalysis, but the inherent weakness of this method is that the sources of bias are not controlled by the method.…”
Section: Comparative Evaluation Of Local Anesthesia Techniques Patienmentioning
confidence: 95%
“…They concluded that because of the large heterogeneity in the contents, design, and outcomes of the studies, the scientific justification for the metaanalysis were not met and they instead used an unconventional consensus-type approach to grade the outcomes based on the methodology proposed by Garbutt et al 107 Recently, Alhassan et al 108 compared patient-perceived pain during cataract surgery for retrobulbar versus peribulbar interventions invoking metaanalysis. Both studies reached the same conclusion that: Retrobulbar and peribulbar blocks perform similarly, and there is little difference between them in terms of patient-perceived pain and anesthesia during cataract surgery.…”
Section: Comparative Evaluation Of Local Anesthesia Techniques Patienmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that one cannot be completely certain that the blockade is really intra- or extraconal (20). There are reports of brainstem anesthesia following PBA (2123), including patients who required tracheal intubation and mechanical ventilation (25). A Cochrane systematic review of RBA versus PBA for cataract surgery also concluded that there is little to choose between the two in terms of anesthesia and akinesia during surgery, measuring acceptability to patients, need for additional injections and development of severe complications (25).…”
Section: Discussionmentioning
confidence: 99%